Post‐stroke family resilience is correlated with family functioning among stroke survivors: The mediating role of patient's coping and self‐efficacy - Wei Zhang; Ya‐Jing Gao; Ming‐Ming Ye; Lan‐Shu Zhou (Wiley, 2024)
Abstract Aim Family resilience and healthy family functioning are crucial for stroke survivors' rehabilitation. This study aimed to determine the mediating effects of self‐efficacy and confrontation coping on the relationship between family resilience and functioning among patients with first‐episode stroke. Design A cross‐sectional design was applied. Methods 288 patients with first‐episode stroke were recruited from 7 hospitals in Shangqiu and Shanghai, China, from July 2020 to October 2020. A shortened Chinese version of the Family Resilience Assessment Scale, family adaptation, partnership, growth, affection and resolve questionnaire, Medical Coping Modes Questionnaire, and Self‐efficacy for Chronic Disease 6‐item Scale were used to collect the self‐reported data. The relationships among the studied variables were studied using spearman correlation and structural equation model. Results The average level of family functioning among stroke patients was 7.87 (SD = 2.32). About 26.8% (n = 76) of patients reported family dysfunction. The structural equation model showed that family resilience directly affected patients' satisfaction with family functioning (r = 0.406, p < 0.001) and indirectly affected the mediating role of patients' self‐efficacy and confrontation coping style (r = 0.119, p < 0.001). The model was with good fit (χ2/df = 2.128, RMSEA = 0.065, GFI = 0.956, AGFI = 0.919, NFI = 0.949, and TLI = 0.956). Conclusion Family resilience and functioning among patients with first‐episode stroke are positively associated with the mediating effects of the patients' confrontation coping style and self‐efficacy between family resilience and functioning. The findings indicate that the professionals should pay special attention to families exhibiting poor family resilience or with patients who rarely use confrontation coping styles or with poor self‐efficacy since they are more likely to suffer from low functioning.